Systematic planning of clinical documentation - Leiner, Florian; Haux, Reinhold (Methods of information in medicine, 1996)
All information obtained from a patient in the course of medical care is a potential part of clinical documentation. The documentation usually serves a number of different purposes. The task of a documentation system is to fulfil these purposes in a methodically correct manner and as economically as possible. This requires that the properties of the documentation system be planned systematically with a view to the goals pursued. To support systematic planning, a “documentation protocol” is proposed analogous to the “study protocol” used for controlled clinical trials. The individual sections of the proposed documentation protocol are described and the design options which exist in the corresponding planning phases are pointed out. Experience gained by the application of the documentation protocol is discussed.